Dissipation, Processing Factors and Dietary Exposure Assessment of Myclobutanil in Tomato - Yanli Qi; Junli Cao; Chunyong Li; Pengcheng Ren; Shu Qin; Jindong Li (Molecules, 2023)
Myclobutanil residue poses a potential threat to consumers’ health. This work aims to investigate the degradation behavior, residue levels, processing factors (PFs) and dietary risk of myclobutanil in tomato. Myclobutanil was analyzed using a modified quick, easy, cheap, effective, rugged, safe (QuEChERS) method combined with ultra-performance liquid chromatography–mass spectrometry (UPLC-MS/MS), and average recoveries ranged from 82% to 102% with relative standard deviations RSDs ≤ 9.1%. After spraying myclobutanil miscible oil under field conditions, the initial concentration of myclobutanil was 0.055 mg/kg, and its dissipation followed the first-order kinetics equation with a half-life of 2.88 days. Myclobutanil was mainly present in the tomato skin, and its concentration was about four times that in the whole tomato. The initial concentration of myclobutanil in raw tomato was 0.100 mg/kg. After washing, peeling, homogenization, simmering and canning, the residual level of myclobutanil decreased to 0.067 mg/kg, 0.023 mg/kg, 0.013 mg/kg, 0.044 mg/kg and 0.041 mg/kg, respectively. Although the procedure of simmering led to an increase in myclobutanil concentration, the PFs were all less than 1 in the whole process, showing that the processing procedure significantly decreased the residual level of myclobutanil canned tomato paste in comparison with the raw agricultural commodity. Washing, peeling, and homogenization played critical roles in reducing pesticide residues. The residues of myclobutanil during the processing of tomato pose low dietary exposure risks to consumers in China, which were acceptable. However, the acute and chronic risk quotient for children revealed that it was necessary to monitor the dietary exposure of pesticide residues for children closely.